IMPLEMENTATION OF SEMARANG CITY REGIONAL REGULATION NUMBER 4 OF 2016 CONCERNING ADMINISTRATION POPULATION REGISTRY IN DATA RECORDING OF NON-PERMANENT POPULATIONS IN TEMBALANG DISTRICT - Caroline Wynne Rahmanto; Retna Hanani (Journal of Public Policy and Management Review, 2021)
Semarang City as one of the metropolitan cities in Indonesia is the destination to find work or take education from the areas around Semarang City, called Kedungsapur (Kendal, Demak, Ungaran, Semarang Regency, Salatiga City and Purwodadi Grobogan Regency) and other cities. People who come to Semarang City and stay for more than 30 days and do not intend to move are referred to as nonpermanent residents. One of them is in Tembalang District, that has one university, which has increasing the nonpermanent residents in Tembalang District. The purpose of this study was to determine the implementation of the nonpermanent residents registration policy and the factors influence the low implementation of the policy, by using the Mazmanian and Sabatier policy implementation model and the factors affecting compliance according to Bierstedt. The method used in this research is qualitative and will be analyzed descriptively. Data collection using interview and documentation techniques. The results of this study indicate that the implementation of the nonpermanent residents registration policy in Tembalang Village has not been implemented in accordance with Semarang City Regulation Number 4 of 2016. The registration of nonpermanent residents in Tembalang Village is still low and very few report to implementing agencies because of the lack of information received by non-permanent residents. The author's recommendation is to conduct further socialization to inform the usefulness and form the habits in society. In addition, it invites partners consisting of boarding house owners and universities to cooperate in recording non-permanent residents.